The Subject And Ways Of Development Of Organic Chemistry. The Main Stages In The Development Of Organic Chemistry - Yusufova Sabina Georgievna (Genius Journals, 2023)
Organic chemistry is of exceptionally important scientific and practical importance. The object of her research is a huge number of compounds of synthetic and natural origin. Therefore, organic chemistry has become the largest and most important branch of modern chemistry. The article discusses about the subject and ways of development of organic chemistry. Furthermore, we will discuss the main stages in the development of organic chemistry
Keywords: Petrochemistry; raw materials